Pain Management in Critical Patient - Altinbas, Ali; Canakci, Ebru (Archives of Clinical and Biomedical Research, 2017)
Pain is a major problem in intensive care and is the primary problem for intensive care patients. The high-quality pain management and pain, palliative treatment should be targeted for every patient. Palliation, evaluation, and monitoring of the pain begin with the use of effective strategies. Pain management includes both pharmacological and nonpharmacological treatments. Analgesia has positive effects on morbidity and prevents pulmonary complications such as atelectasis and pneumonia, and self-extubation after agitation. In this review, assessment, monitoring, results, and method of the pain management in intensive care unit (ICU) were explained.